Engaging Beyond Academia : A Call to Act for Environmental Scientists - Graham, Olivia J.; Griffiths, Laura; Münzner, Karla ; 0000-0002-7568-8095; Selak, Lorena; Barbosa, Carolina C.; Cai, Xun; Ogashawara, Igor; Sun, Xinyu; Thellman, Audrey (Limnology and Oceanography Bulletin, 2025)
The future of our planet relies on scientists' ability to effectively translate knowledge into action, and researchers have an imperative commitment to leverage their understanding. As aquatic early career researchers (ECRs), we draw upon personal experiences to share our learnings about how individuals can drive change. We showcase diverse approaches for ECRs to create meaningful impacts by connecting with other researchers, broader society, and decision-makers. At the same time, institutional challenges inhibit scientific engagement beyond academia, particularly for ECRs. Such barriers include (1) lack of value and support for engagement activities, (2) limited training opportunities, (3) research siloes, and (4) rigid funding structures. We offer potential systemic solutions, from developing and adopting new performance metrics for academic researchers to enhanced flexibility with grant timelines and spending. Academic systems need to change and so does the way scientists engage. Our future depends on it.
Publisher Copyright: © 2024 The Author(s). Limnology and Oceanography Bulletin published by Wiley Periodicals LLC on behalf of Association for the Sciences of Limnology and Oceanography.